Pelatihan dan Konsultasi Manajemen, Bisnis dan Keuangan bagi UMKM Kalibata - Azizul, Azizul; Fortune, Dewi (Fakultas Ekonomi dan Bisnis Islam, 2023)
This dedication is motivated by the low knowledge of UMKM actors in running the business, especially during the Pandemic. The purpose of this service is to train UMKM actors to develop competencies in business and financial management and increase the competitiveness of UMKM actors in the current era of globalization. This service method uses the seminar and training method. The result of this service is that UMKM actors are able to understand the concept of business and financial management in a simple way to run their business. The implication of this service is a reference by UMKM actors to increase the value of their business by implementing proper business and financial management.